تاريخ الحرب العسكرية في أحكام الشريعة الإسلامية والقانون الدولي: History of Military War in the Provisions of Islamic and International Law - Mohammad al-Malyan, Syaimak; Mohd Nor, Ruzman (Al-Muqaddimah: Online Journal of Islamic History and Civilization, 2018)
Since human being landed on earth, force and violence were used as a tool to ensure individuals survival. It has become the right in system of war to empower protection for the benefit of the aggressed state upon its quest to repel the attack from the other state. The legality of using force and initiating war is basically scaled according to the degree of the self-defense right. In addition, there are cases and situations where strict application of the criteria for the right to the war could lead to the impossibility of achieving the aims and purposes of the war’s law. In such cases, need to be considered in the international law to test it proportionally under the law of war as a part in testing the suitability in order to wage war. The absence of effective international law that govern the use of force and initiating wars. While the provision of the Islamic law and its principles of tolerance has provided detailed controls that deal with war since several centuries. The basic upon which Islam rely is peace between people rather than war.